The human EDAR 370V/A polymorphism affects tooth root morphology potentially through the modification of a reaction–diffusion system - Kataoka, Keiichi (Sci Rep, 2021)
Morphological variations in human teeth have long been recognized and, in particular, the spatial and temporal distribution of two patterns of dental features in Asia, i.e., Sinodonty and Sundadonty, have contributed to our understanding of the human migration history. However, the molecular mechanisms underlying such dental variations have not yet been completely elucidated. Recent studies have clarified that a nonsynonymous variant in the ectodysplasin A receptor gene (EDAR 370V/A; rs3827760) contributes to crown traits related to Sinodonty. In this study, we examined the association between the EDAR polymorphism and tooth root traits by using computed tomography images and identified that the effects of the EDAR variant on the number and shape of roots differed depending on the tooth type. In addition, to better understand tooth root morphogenesis, a computational analysis for patterns of tooth roots was performed, assuming a reaction–diffusion system. The computational study suggested that the complicated effects of the EDAR polymorphism could be explained when it is considered that EDAR modifies the syntheses of multiple related molecules working in the reaction–diffusion dynamics. In this study, we shed light on the molecular mechanisms of tooth root morphogenesis, which are less understood in comparison to those of tooth crown morphogenesis.